Financial constraints and innovation: why poor countries don't catch up - Yuriy Gorodnichenko; Monika Schnitzer (Institute for the Study of Labor (IZA), 2010)
This paper examines micro-level channels of how financial development can affect macroeconomic outcomes like the level of income and export intensity. We investigate theoretically and empirically how financial constraints affect a firm's innovation and export activities, using unique firm survey data which provides direct measures for innovations and firm-specific financial constraints. We find that financial constraints restrain the ability of domestically owned firms to innovate and export and hence to catch up to the technological frontiers. This negative effect is amplified as financial constraints force export and innovation activities to become substitutes although they are generally natural complements.
Keywords: O3; O16; F1; G3; 330; Innovation; productivity; financial constraint; export; technology frontier; BEEPS; Verschuldungsrestriktion; Finanzsektor; Entwicklung; Innovation; Exportindustrie; Technische Effizienz; Produktivität; Entwicklungskonvergenz; Theorie; Entwicklungsländer